Adaptasi Guru Terhadap Kebijakan Kurikulum Merdeka Belajar di SMA Negeri 5 Kupang - Marlon Nofyanto Naitboho; Arifin (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
This study aims to determine teacher adaptation to the independent learning curriculum policy and the obstacles to the independent learning curriculum policy for teachers at SMA Negeri 5 Kupang. This research used a descriptive-qualitative approach. The subjects of this study were school principals, curriculum representatives, and teachers. Data collection techniques in this study were carried out through observation, interviews, and documentation. Data analysis techniques use data reduction, data display, and verification. The results of the study found obstacles to the independent learning curriculum policy for teachers, namely: (1) the quality of the teacher's human resources, who do not fully have competence in minimal learning; (2) the facilities and learning resources are minimal, or the infrastructure is not yet adequate, and teachers are technology stuttering; and (3) the selection of subjects the students are not given the freedom to choose according to their interests, talents, and abilities.